An Exploration of the Nordic Model - de Buitleir, Donal (Statistical and Social Inquiry Society of Ireland, 2010)
In this paper I examine the social and economic system which is generally known as the Nordic Model and compare this with the Irish case. The analysis is limited to Denmark, Finland and Sweden as Norway and Iceland may be regarded as special cases due to their non-membership of the EU and their heavy dependence on oil and fishing respectively. One of the important advantages claimed for the Nordic model is that high levels of security go hand in hand with flexibility and a willingness to change. In Ireland it seems that the reverse is often the case. The most radical changes are accepted by those with the least security while the pace of reform is slow in the public sector and the most secure parts of the private sector. Given our current difficulties it is reasonable to expect that those in secure employment show the greatest willingness to embrace change and that is something we should insist on.
(Presidential Address read before the Society, 20 May 2010)
Keywords: Nordic model; comparative statistics; Ireland; 314.15